Immune-related keratitis is a rare complication associated with nivolumab treatment in a patient with advanced colorectal cancer: A case report - Su, Yuqi; Li, Guoquan; Xu, Jiaxin; Zheng, Jiale; Jiao, Jiapeng; Zhang, Jianhui; Gu, Xiaokang; Cai, Zhai; Luo, Hongyu; Li, Zhou; Han, Shuai (Frontiers in Oncology, 2022)
Background Immunotherapy has been widely used to treat Colorectal cancer but has also observe some immune-related adverse effects. With proper treatment, most irAE can be solved and the effect of immunotherapy will not be affected by temporary immunosuppression. However, there are few reports about corneal irAE, and the current understanding of irAE is incomplete. Here we report a metastatic colorectal cancer case of immune-related keratitis caused by nivolumab and to explore the occurrence of immune-related keratitis. Case description: Here we report the case of a 49-year-old man with mCRC who had no previous ocular disease but developed immune-related ulcerative keratitis after treatment with nivolumab. We summarize a large amount of literature to discuss the mechanism of immune-related keratitis. In addition, we conclude a method that may be used to detect the occurrence of immune keratitis, by monitoring MMPs and maspin in patients treated with nivolumab. We believe immune-related keratitis may be a rare complication of nivolumab in the treatment of mCRC. The effect of simple anti-infective therapy and repair-promoting drugs was not obvious, but the effect of glucocorticoid combined with autologous serum was significant. Conclusion: The mechanism of immune-related keratitis is that nivolumab destroys the immune microenvironment and ACAID, and affects corneal healing. Patients who use nivolumab can prevent immune keratitis by testing MMPs and maspin. The occurrence of immune keratitis may be a good indicator of the efficacy of ICI, and further study can be done in the follow-up